An exciton-polariton bolometer for terahertz radiation detection - Paschos, G. G. (2018)
We experimentally investigate the feasibility of a bolometric device based on exciton-polaritons. Initial measurements presented in this work show that heating – via thermal expansion and bandgap renormalization – modifies the exciton-polariton propagation wavevector making exciton-polaritons propagation remarkably sensitive to thermal variations. By theoretical simulations we predict that using a single layer graphene absorbing layer, a THz bolometric sensor can be realized by a simple exciton-polariton ring interferometer device. The predicted sensitivity is comparable to presently existing THz bolometric devices with the convenience of being a device that inherently produces an optical signal output.